2017
DOI: 10.4038/gmj.v22i2.7968
|View full text |Cite
|
Sign up to set email alerts
|

Generative concern; a promising health promotion component for well-being of the elderly in Galle, Sri Lanka

Abstract: Introduction: Population of Sri Lanka is aging fast. Chronic diseases in the elderly have become a vital public health issue. Generativity, concern for teaching and nurturing the next generation, is identified as an important component of well-being of the elderly. This study assessed the generative concern in a sample of elders in Galle, and correlates of the construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Psychological health was affected by five out of the ten chronic diseases we explored in this study. The negative impact of comorbidities on psychological health was shown previously, 37 while cancer and stroke have the greatest effect on reducing psychological well-being. Santhalingam et al 52 and Kumar et al 3 showed that musculoskeletal disorders decrease the overall QOL and social interactions.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Psychological health was affected by five out of the ten chronic diseases we explored in this study. The negative impact of comorbidities on psychological health was shown previously, 37 while cancer and stroke have the greatest effect on reducing psychological well-being. Santhalingam et al 52 and Kumar et al 3 showed that musculoskeletal disorders decrease the overall QOL and social interactions.…”
Section: Discussionmentioning
confidence: 52%
“…We also found that financial independence increases the overall QOL and domain-specific QOL of older people, which is supported by most other studies. 2–5 21 35 36 As 61% of the Sri Lankan older people had no regular paid job, 37 encouraging and supporting them towards income-generating activities would make them financially independent and economically productive and thereby improve their QOL. It is noteworthy that the majority (70%) in this study belonged to the youngest segment (65–74 years), but only 3.6% were self-employed, which clearly indicates that introducing supportive services to establish income-generating activities matched to their physical abilities would make a positive impact.…”
Section: Discussionmentioning
confidence: 99%